1999
DOI: 10.1016/s0370-2693(99)00967-3
|View full text |Cite
|
Sign up to set email alerts
|

Ramond-Ramond couplings on brane-antibrane systems

Abstract: Couplings between a closed string RR field and open strings are calculated in a system of coincident branes and antibranes of type II theory. The result can be written cleanly using the curvature of the superconnection. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
179
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(185 citation statements)
references
References 27 publications
6
179
0
Order By: Relevance
“…• Considering that the dynamics is controlled by a tachyon world-volume action automatically provides the model with a WZ term of the form given in [37,66,67]. We have not discussed this term at all in this work, but in [24] it was shown that properties like discrete symmetries (parity and charge conjugation) and anomalies are, in general, correctly described by analyzing this term.…”
Section: Jhep11(2010)123mentioning
confidence: 97%
“…• Considering that the dynamics is controlled by a tachyon world-volume action automatically provides the model with a WZ term of the form given in [37,66,67]. We have not discussed this term at all in this work, but in [24] it was shown that properties like discrete symmetries (parity and charge conjugation) and anomalies are, in general, correctly described by analyzing this term.…”
Section: Jhep11(2010)123mentioning
confidence: 97%
“…• Considering that the dynamics is controlled by a tachyon world-volume action automatically provides the model with a WZ term of the form given in [35][36][37]50]. In [15] it was shown that properties like discrete symmetries (parity and charge conjugation) and anomalies are, in general, correctly described by analyzing this term and we will detail them also here.…”
Section: Jhep02(2012)064mentioning
confidence: 99%
“…It also includes tachyon part for the case of the D9-antiD9 system which was conjectured in [52] and derived in [4,5]. The open superstring massive modes show up in our general RR charge formula such that the quantization of the RR charge is ensured.…”
Section: Jhep03(2015)077mentioning
confidence: 64%